Studnicki-Gizbert, Daviken. A Nation upon the Ocean Sea: Portugal’s Atlantic Diaspora and the Crisis of the Spanish Empire, 1492-1640. New York: Oxford University Press, 2007, x + 242 pp. - Ebert, Christopher (2007)
La reseña no presenta resumen.